The Diamond Fraud Theory for Property and Real Estate to Detect Financial Report Fraud - Erisa Aprilia Wicaksari; Syam Widia; Vini Wiratno Putri (Management Analysis Journal, 2023)
The purpose of this study is to examine the role that fraud diamond components play in identifying financial statement fraud in businesses in the real estate and property sectors. Purposive sampling was employed to choose the sample, and a total of 55 firms were included in the sample. Using the STATA tool, panel data regression was used for the analysis. Financial target, represented by ROA, external pressure, represented by Debt to Equity Ratio, external pressure, represented by Debt to Total Asset Ratio, nature of the industry, represented by Receivable, ineffective monitoring, represented by the number of board directors, ineffective monitoring, represented by Related Parties Receivable, rationalization, represented by Accrual to Total Asset Ratio, represented by Auditor Replacement. Capability are the independent variables in this study. Financial statement fraud is the dependent variable, while earning management is the proxy. The outcome demonstrated that the nature of the industry and rationalization had an impact on financial statement fraud.